Complete dressmaking skills - Knight, Lorna (Hauppauge, New York Barron's Educational, 2014)
"Starting with the essentials for new sewers--from common terminology to the basics on equipment, fabric, and stitching --Complete Dressmaking Skills offers in-depth guidance and step-by-step instruction on everything readers need to know about making their own garments, including: Sewing zippers, cuffs, piping, collars, pockets, yokes, fastenings, and other necessities ; Tips on buying, using and making your own patterns"--Provided by publisher.
Keywords: Sewing; Dressmaking